Patient Satisfaction and Preference for Metered-Dose Inhalers vs. Dry Powder Inhalers in the Treatment of Obstructive Airway Disease - Sobia Rehman; Mehreen Umair; Kaleemullah; Abdul Rehman Azam; Mujahid Hussain; Sohail Akhtar (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: To evaluate patient preference for different inhaler devices in the treatment of obstructive airway disease (OAD). METHODOLOGY: This cross-sectional study was conducted at the Department of Pulmonology, Indus Hospital, Korangi Campus, Karachi, Pakistan, from July 2023 to January 2024. A non-probability, consecutive sampling technique was adopted. The inclusion criteria were patients aged 18-70 years presenting with OADs, regardless of disease duration, and using either a metered dose inhaler (MDI) or a dry powder inhaler (DPI). Patients who were using pressured MDI (pMDI) were given DPI containing the same drugs at the exact dosage for two weeks. Patients who were using DPI were given pMDI containing the same medications at the precise dosage for two weeks. Patients were trained on the techniques for using the inhalers, and the patient preference between two inhaler devices was determined using the PASAPQ questionnaire. Data analysis was performed using SPSS 26.0. RESULTS: In a total of 100 patients, the mean age was 51.64±13.52 years. There were 59 (59.0%) male patients. Forty-nine percent of patients had COPD, whereas asthma was present in 51 (51.0%). Out of 100 patients, 50 (50%) were using MDI inhalers, and 50 (50%) were using DPI inhalers. The mean PASAPQ scores were significantly higher in terms of satisfaction (p = 0.0002), performance (p = 0.0002), and convenience (p = 0.0374) domains for DPI inhalers. CONCLUSION: The DPI inhalers were associated with higher levels of satisfaction, performance, and convenience compared to MDI inhalers in the management of oral antidiabetic medications (OAD).